Characteristics and Potential Roles of Natural Killer Cells During SARS-CoV-2 Infection. Issue 1 (19th January 2023) - Cao, Wen-Jing; Wang, Fu-Sheng; Song, Jin-Wen
Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a tremendous burden on public health and world economies. An efficient host immune response to acute SARS-CoV-2 infection requires rapid and early activation of the innate immune system. Natural killer (NK) cells represent a critical component of the innate immunity. Here, the appearance of CD56 - CD16 + NK cells and unconventional CD56 dim CD16 neg NK cells during the course of SARS-CoV-2 infection, and the phenotype and effector functions of NK cells during SARS-CoV-2 infection were summarized. The involvement of the dysregulated NK cells in the immunopathogenesis of the coronavirus disease 2019 (COVID-19) and clinical trials of adoptive NK cell–based therapies against COVID-19 were also discussed.